Robust Path Construction for Reliable Data Transmissions in Node Disjoint Multipath Routing - Abdulaleem Ali ALmazroi; MA Ngadi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
Wireless Sensor Networks (WSNs) are prone to node breakdowns due to energy constraints, which contribute to frequent topology changes. Moreover, since sensor nodes have restricted transmission range, multiple hops are needed by the node in order to forward the packets from one node to the other and this raises very challenging issues when designing routing protocols. Most of the proposed single path routing schemes use a periodic low-rate flooding of data in order to recover from path failures, which causes higher consumption in sensor node resources. So multipath routing is an optimal approach to enhance the network lifetime. In this paper, a robust path construction for a reliable data transmission in node-disjoint multipath routing (RNDMR) is proposed for WSNs. The proposed RNDMR has the ability to provide a low overhead path construction as well as provide data transmission reliability by using XOR-based coding algorithm, which entails low utilization of resources, such as low storage space and lesser computing power. In the proposed RNDMR, the procedure involves the splitting up of all transmitted messages into many different segments of equal size, before adding the XOR-based error correction codes and distributing it among multiple paths simultaneously in order to boost reliable data transmission and to be assured that the essential fragment of the packet arrives at the sink node without any additional consumption of energy and undue delay. By using simulations, the performance of RNDMR was assessed and compares it with ReInForm routing. The results illustrate that RNDMR attains low energy consumption, records low average delay and routing overhead, as well as increased packet delivery ratio when compared with ReInForm Routing.